Effect of Selected Entomopathogenic Fungal Species on Embryonic Development of Ascaris suum (Nematoda) - Kinga Mazurkiewicz-Zapałowicz; Bogumiła Pilarczyk; Lidia Kołodziejczyk; Cezary Tkaczuk; Magdalena Twarużek; Łukasz Łopusiewicz; Jan Grajewski; Ewa Dzika; Elżbieta Kalisińska (Animals, 2023)
The aim of the study was to evaluate the potential of using five selected species of entomopathogenic fungi (Beauveria bassiana, B. brongniartii, Conidiobolus coronatus, Isaria fumosorosea, and Metarhizium robertsii) in the bioregulation of the dispersive stages of the parasitic nematode—Ascaris suum. Experimental cultures of each of the selected entomopathogenic fungi, as well as a control culture without fungi, were incubated with A. suum eggs at 26 °C for 28 days. Development of the A. suum eggs was observed using a light microscope on the 7th, 14th, 21st, and 28th days of incubation. The API-ZYM® test was used to determine, semiquantitatively, the activity of 19 hydrolytic enzymes from the entomopathogenic fungi. The cytotoxicity of the fungi was determined using tetrazole salt MTT. It was found that none of the five tested strains of entomopathogenic fungi showed an ovicidal effect, and none of them colonized the A. suum egg shells. However, ovistatic activity was observed mainly until the 14th day of incubation by I. fumosorosea, M. robertsii, and B. bassiana. In the MTT test, M. robertsii showed moderate cytotoxicity, while the other species showed low cytotoxicity. Among the strains tested, I. fumosorosea showed the highest spectrum of hydrolase production (13 out of 19 enzymes gave a positive reaction from 3 to 5; 20–40 nM or more). The absence of morphological changes in the A. suum egg shells suggests that the antagonistic effect of the studied entomopathogenic fungi may be due to their cytotoxicity, associated with the production of secondary metabolites—toxins (M. robertsii) and enzymatic activity (I. fumosorosea).